The modern state of elms (Ulmus L., Ulmaceae) in arboretum of Peter the Great Botanic Garden under conditions of epiphytoty of the Dutch elm disease - Firsov Gennadii; Bulgakov Timur (Hortus Botanicus, 2017)
The dying of elms (Ulmus L.) at Peter the Great Botanic Garden of the Komarov Botanical Institute RAS in Saint-Petersburg has been observed since the beginning of the 1990’s, soon after the considerable St.-Petersburg climate warming in 1989. During the period from 1981 (the year of the last total inventory of the Botanic Garden) to 2015 three hundred and eighty five trees died, were cut down and removed. They belonged to 12 Ulmus biological and cultivars species: U. laevis – 317 (11 trees are still alive, but all of them are infected, stem dried out from 25 to 70%), U. glabra – 40 (died completely in 2013); U. glabra ‘Camperdownii’ – 6 (died completely in 2014); U. minor – 6 (died completely in 2011); U. аmericana – 4 (died in 2007); U. × hollandica ‘Wredei’ – 3 (died in 2013); U. macrocarpa – 2 (died in 2006); U. pumila ‘Argenteo-variegata’ – 2 (died in 2007); U. japonica – 2 (1 tree is still alive); U. laciniata – 1 (died in 2015); U. parvifolia – 1 (3 trees are still alive); U. pumila – 1 (5 trees are still alive). The most severe dying began after abnormally warm winter 2006/07, the largest amount died in 2013. The most resistant to Dutch elm disease taxa were U. parvifolia and U. pumila. Further research is needed for other two taxa (U. × arbuscula and U. japonica). Selection of elms for resistance to Dutch elm disease seems to be possible. Frost damaging of many exotic tree species in St.-Petersburg has been considerably diminished because of climate warming during the previuos decades. However, introduction of some species is became limited by new negative factors, especially biotic ones (new plant diseases and pests). The future arboreal species assortment for parks and gardens of St.-Petersburg and surrounding settlements should be considerably revised in respect to this climate change.